21st century Northern Hemisphere warming in a 2025-year context of climatic events using tree-ring data - Helama, Samuli (Springer Nature, 2026)
In this study, previously built community ensemble reconstruction, fully based on tree-ring proxy data, is used as a precisely estimated preindustrial-to-present-day temperature scale for Northern Hemisphere summer (June through August) variability over the past two thousand years, against which the recent variability in the observed record was evaluated. The proxy data verified successfully against temperature variability defined by grid boxes extending the tree-ring sites by plus/minus 10 degrees latitudinally and longitudinally (but not over wider spatial scales) over the 1921–2010 period. Summer 2024 was the warmest in the instrumental record, 2.8 °C above the preindustrial 1850–1900 reconstruction mean. In comparison, the warmest and coldest reconstructed summers in AD 246 and AD 536 were, respectively, 1.5 °C and 5.5 °C colder than the 2024 warmth. This means that the full range of natural climate variability was 4.0 °C, which was increased to 5.5 °C by 21st century warming. Temporal pattern of the warmest and coldest preindustrial 1-year temperature events reflected the long-term climatic swings previously described in paleoclimate literature through the Roman Warm Period, AD 536/540s event, Mediaeval Warm Period and Little Ice Age. Despite the improvements in the data processing, the reconstruction still contains considerable uncertainties. A future aim should be to develop denser tree-ring networks to fully cover the extra-tropical Northern Hemisphere land temperature grid boxes for an improved evaluation of the preindustrial and 21st century climatic events, for which purpose the Roman Warm Period appears an interesting, yet largely unexplored, climatic feature.
Keywords: dendrochronology; dendroclimatology; Northern Hemisphere; climate changes; climate history; verification